Study Of Purity And Recovery Of Carbon Dioxidefrom Binary Mixture Of Natural Gas Usingdifferent Adsorbents In Pressure Equalizedpressure Swing Adsorption - Chong, Ching Yang (Universiti Sains Malaysia, 2017)
The separation effect of methane (CH4) and carbon dioxide (CO2) which is binary mixture of natural gas was investigated with characterization tests, breakthrough study and pressure swing adsorption (PSA) process. 2 types of adsorbent were studied and compared which were activated charcoal and zirconium-benzenedicarboxylate (UiO- 66). The characterization tests showed that UiO-66 has higher BET surface area and activated charcoal has higher fixed carbon content. For breakthrough study, the breakthrough curves were obtained under the condition of 1 bar and room temperature. The effects of both adsorbents and different inlet gas ratio were investigated. UiO-66 has larger adsorption capacity proven by its longer breakthrough time. Besides, PSA process had utilized 2-bed adsorption under the conditions of 3 bar and room temperature. However, separation effect of this mixture was not effective and commercially attractive because 2 types of adsorbent used were not suitable for separating this binary gas. Hence, the purity was not achieved but the recovery could be obtained because UiO-66 showed more than 90% recovery on CO2.